Antitrypanosomal Potential of Wonderful Kola Methanolic Extract Against Trypanosoma brucei brucei - Rufa’i, F.A.; Yerima, A.B.; Sani, H.H. (International Journal of Scientific Research in Biological Sciences, 2023)
Several pharmacognostic properties of wonderful kola plant has necessitated the need for a high-throughput identification of bioactive compounds present in this plant which could serve as lead compounds in developing potent and novel trypanocidal agents. Trypanosomiasis is a protozoal disease known as sleeping sickness which is ranked among top priority tropical infections. The aim of the current study was to identify the bioactive compounds present in methanolic extract of wonderful kola and determine its antitrypaosomal activity. Photochemical screenings and Gas Chromatography Mass Spectrometric Analysis of the plan extracts was carried out to determine the bioactive compounds. A total of 12 adult rats, 7 weeks old of both sexes were randomly divided into six groups (1, 2,3,4,5 and 6) of 2 animals each. All the Groups were intraperitoneally infected with 0.1 mL of blood containing 106 Trypanosomes/mL. Groups 1- 4 received methanolic extract of wonderful kola intraperitoneally at daily doses of 0.01, 0.1, 1.0 and 10 mg/mL/kg body weight, while Group 5 received standard trypanosomal drug of 7.86 mg/kg (suramin dose) which served as the positive control and Group 6 was infected without any treatment (negative control). Different pathological parameters in terms of parasitemia, temperature, weight and percentage of survival were all evaluated. Some of the compounds identified include: saponins, tanins, glycosides, terpenoids, steroids, alkaloids, flavonoids, benzendodecanoic acid, methyl tetradecanoate, hexadecanoic acid, diisooctyl adipate, cycloheptatien. Among the animals treated with methanolic extract of wonderful kola, there was decrease in the level of parasitaemia, decrease from higher to normal body temperature, increases in body weight and survival rate. In conclusion, Wonder Kola contains important bioactive compounds which are relatively safe and could be regarded as potential Trypanocidal agents in the treatment of trypanosomiasis.